Use of zinc salts of DMTD in coating compositions

JP7652994B2Active Publication Date: 2025-03-27AKZO NOBEL COATINGS INT BV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024541201
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-17
Filing Date
2023-01-17
Publication Date
2025-03-27
Estimated Expiration
2043-01-17

Smart Images

  • Figure 0007652994000016
    Figure 0007652994000016
  • Figure 0007652994000017
    Figure 0007652994000017
  • Figure 0007652994000001
    Figure 0007652994000001
Patent Text Reader

Abstract

The present invention relates to the use of a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD) in a coating composition further comprising a metal salt thereof and a resin system comprising a) an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin, and b) a lithium salt having a solubility in water ranging from 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate, for enhancing the barrier function of a protective layer generated as a result of the presence of the lithium salt in the coating composition when used on a metal substrate coated with the coating composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the use of zinc salts of DMTD in coating compositions having protective properties, particularly useful for metal substrates. [Background technology]

[0002] Protective coatings are widely used to protect substrates, especially metal substrates, from corrosion. Hexavalent chromium compounds have long been used as corrosion inhibitors in protective coatings and conversion treatments of metal surfaces. However, hexavalent chromium is toxic and is therefore scheduled to be phased out for environmental, worker safety, and regulatory reasons. Although alternative chromium-free inhibitors have been proposed in recent years, many formulations struggle to meet the corrosion resistance standards, especially in industry.

[0003] Although much progress has been made in chromium substitution in corrosion protection coatings, it remains desirable to provide Cr-free coatings that have improved long-term corrosion resistance properties that are equivalent to or better than conventional Cr-containing coatings.

[0004] Recently, coating compositions with lithium salts have been proposed as an alternative to Cr-containing coatings. See, for example, "Chemical Properties of Coatings with Lithium Salts," IEEE Transactions on Materials Science and Engineering, Vol. 13, No. 1, pp. 1171-1175, 2002. As described in this paper, coating compositions with lithium salts have been demonstrated to have anticorrosive activity due to the formation of a protective layer on the substrate metal at locations where the coating deposited from the coating composition with lithium salt has defects. Such a layer was found to contain aluminum, oxygen and lithium that have leached from the coating. The protective layer provides a barrier between the metal surface at the coating defect and the corrosive environment. This barrier function and the strength of this protective layer may be important for long-term protection. Insufficient barrier function or low strength of the formed protective layer may result in localized metal defects and corrosion.

[0005] It is desirable to provide coating compositions that have improved barrier properties. [Prior art documents] [Non-patent literature]

[0006] Visser, P., Liu, Y., Terryn, H. et al. “Lithium salts as leachable corrosion inhibitors and potential replacement for hexavalent chromium in organic coatings for the protection of aluminum alloys” J Coat Technol Res 13, 557-566 (2016) Summary of the Invention

[0007] The inventors have found that when the coating composition also contains a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the protective layer formed on the coating defects by the action of the lithium salt exhibits significantly higher barrier function as observed by electrochemical impedance spectroscopy (EIS). The zinc salt of DMTD acts as an enhancer of the barrier function of the protective layer formed on the exposed metal surface.

[0008] The present invention therefore relates to the use of a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the zinc salt of DMTD being 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII), comprising the metal salt and a) a resin system comprising an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin; b) a lithium salt having a solubility in water in the range of 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; In a coating composition further comprising To enhance the barrier function of a protective layer produced as a result of the presence of a lithium salt in a coating composition when used on a metal substrate coated with the coating composition; The use of the zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD) is provided. [Brief description of the drawings]

[0009] [Figure 1] 1 shows the results of EIS measurements of coating compositions according to some embodiments of the present invention. [Diagram 2] 1 shows the results of EIS measurements of coating compositions according to some embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Surprisingly, it has been found that the use of zinc salts of DMTD enhances the protective layer formed by lithium ions on the metal surface at coating defects when used with lithium salts selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate in the coating composition. The formation of a protective layer by lithium ions has previously been shown to be the mechanism of corrosion protection of lithium salts. When a coating defect forms in a cured coating, thus exposing the metal substrate and making it susceptible to corrosion, lithium ions leach from the coating to the metal surface and contribute to the formation of a protective layer at the surface. The presence of such a protective layer can be seen and its properties quantified using electrochemical impedance spectroscopy (EIS). See, e.g., "Electrochemical Properties of Coatings with Highly Active Protective Mechanisms (Leaching)" by DMTD, et al., "Electrochemical Properties of Coatings with Highly Active Protective Mechanisms (Leaching)," vol. 1, No. 1, pp. 1111-1115, 2002. This electrochemical method allows for the quantification of the barrier properties of the protective layer at the damaged area (scribe) created by the active protective mechanism of the coating (leaching) after exposure to accelerated corrosion tests (e.g., neutral salt spray exposure).

[0011] The magnitude of the barrier function is derived from the electrochemical impedance spectrum. The impedance modulus plot is the impedance modulus (Ω cm) as a function of frequency range (Hz). 2 ) The increase in impedance coefficient in the mid-frequency range 10 Hz can be related to the formation of a protective layer in the damaged area (scribe). The increase in impedance coefficient at low frequencies (10 mHz) can be related to the inhibition of corrosion processes at the substrate. An important advantage of using EIS is the ability to quantify differences between coating formulations that cannot be observed or quantified by visual methods.

[0012] The inventors have tested many compounds and found enhancing agents that enable the protective layer formed by the lithium salt to exhibit significantly higher barrier function. The inventors believe that such enhanced protective layer provides better and / or longer protection of the metal substrate. Here, a higher barrier function is defined as a higher impedance modulus (Ωcm) for the same frequency range (Hz). 2 ), specifically, a higher impedance modulus for frequencies of 10 Hz and 10 mHz as measured by EIS.

[0013] The coating compositions for use in the present invention are preferably chromium-free. By "chromium-free" is meant in particular the absence of any Cr compounds, such as Cr(VI) compounds, e.g. from chromates.

[0014] The coating composition for use in the present invention comprises a) a resin system comprising an organic film-forming resin and, optionally, a curing agent reactive with the organic film-forming resin. Within this specification, the term "film-forming resin" includes not only polymers but also monomers or oligomers that form a polymer system during curing of the coating. By organic film-forming resin, it is meant that the polymer, monomer or oligomer is organic (carbon-containing compound). The coating composition is preferably free of polysiloxanes. The coating composition is preferably not a sol-gel composition.

[0015] The film-forming resin may be selected, for example, from epoxy resins, hydroxy-functional resins (such as polyesters and poly(meth)acrylates), resins with one or more blocked hydroxyl groups (such as acetals), oxazolidine resins, carboxylic acid-functional resins), polyacrylates, polyurethanes, polyethers, polyaspartic esters, (blocked) isocyanates, thiol-functional resins, amine-functional resins, amide-functional resins, imide-functional resins (e.g., maleimides), alkyd resins, resins containing at least one olefinically unsaturated bond, silane-containing resins, polysiloxane resins, acetoacetate resins, functional (curable) fluorinated resins, and mixtures and hybrids thereof.

[0016] Preferably, the film-forming resin is selected from the group consisting of epoxy resins and hydroxy-functional resins, such as hydroxy-functional poly(meth)acrylates or polyester polyols, and polyurethanes. Epoxy resins are epoxy-functional polymers with an epoxy equivalent weight greater than 1, usually about 2. The most commonly used epoxy resins are polyglycidyl ethers of cyclic polyols, such as bisphenol A, resorcinol, hydroquinone and catechol, or polyglycidyl ethers of polyols, such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-bis(hydroxymethyl)cyclohexane. The hydroxy-functional resins preferably have a hydroxy functionality of 2.1 to 3.5 and an equivalent weight of at least 200 g / mol, based on solids.

[0017] Epoxy resins and polyurethanes are preferred film-forming resins for use in the present invention.

[0018] The film-forming resin is preferably present in the coating composition for use in the present invention in an amount of from 1 to 99% by weight, more preferably from 10 to 90% by weight, and even more preferably from 20 to 80% by weight, based on the total weight of the non-volatile components of the coating composition.

[0019] In some embodiments, the coating composition may further contain a curing agent reactive with the film-forming resin. The curing agent contains a functional group reactive with the functional group of the resin. The type of curing agent depends on the nature of the film-forming resin. The curing agent suitable for a particular film-forming resin is common knowledge to those skilled in the art. For example, an acetoacetate resin-based coating composition preferably contains a ketimine-based curing agent.

[0020] The epoxy resin-containing composition preferably contains an aliphatic or aromatic amine curing agent, a polyamide curing agent, a thiol-based curing agent. Suitable epoxy resins are bisphenol A, bisphenol F, bisphenol A / F, novolac and aliphatic epoxy resins. Suitable amine curing agents are aliphatic amines and their adducts (e.g., Ancamine® 2021), phenalkamines, cycloaliphatic amines (e.g., Ancamine® 2196), amidoamines (e.g., Ancamide® 2426), polyamides and their adducts, and mixtures thereof. The epoxy / NH molar ratio in the epoxy amine-type coating composition is preferably in the range of 0.6 to 2.0, more preferably 0.8 to 1.7. For solvent-based epoxy amine coating compositions, the epoxy / NH molar ratio is preferably in the range of 0.6 to 1.4, more preferably 0.8 to 1.2, and most preferably 0.85 to 1.1. For aqueous coating compositions, the epoxy / NH molar ratio is preferably in the range of 0.6 to 2.0, more preferably 0.9 to 1.7, and most preferably 1.3 to 1.7.

[0021] Preferred curing agents for hydroxy-functional resins are isocyanates and isocyanurates. Suitable isocyanate curing agents include aliphatic, cycloaliphatic and aromatic polyisocyanates, such as trimethylene diisocyanate, 1,2-propylene diisocyanate, tetramethylene diisocyanate, 2,3-butylene diisocyanate, hexamethylene diisocyanate, octamethylene diisocyanate, 2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, dodecamethylene diisocyanate, α,α'-dipropyl ether diisocyanate, 1,3-cyclopentylene diisocyanate, 1,2-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 4-methyl-1,3-cyclohexylene diisocyanate, 4,4'-dicyclohexylene diisocyanate methane, 3,3'-dimethyl-4,4'-dimethyl ether diisocyanate, ... These polyisocyanates include cyclohexylene diisocyanate methane, m- and p-phenylene diisocyanate, 1,3- and 1,4-bis(isocyanatomethyl)benzene, 1,5-dimethyl-2,4-bis(isocyanatomethyl)benzene, 1,3,5-triisocyanatobenzene, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,4,6-toluene diisocyanate, α,α,α',α'-tetramethyl o-, m-, and p-xylylene diisocyanate, 4,4'-diphenylene diisocyanate methane, 4,4'-diphenylene diisocyanate, 3,3'-dichloro-4,4'-diphenylene diisocyanate, naphthalene-1,5-diisocyanate, isophorone diisocyanate, transvinylidene diisocyanate, and mixtures of the aforementioned polyisocyanates.

[0022] Adducts of polyisocyanates are also suitable curing agents, such as biurets, isocyanurates, allophonates, uretdiones, and mixtures thereof. Examples of such adducts are the adduct of two molecules of hexamethylene diisocyanate or isophorone diisocyanate to a diol, for example ethylene glycol, the reaction product of three molecules of hexamethylene diisocyanate with one molecule of water, the adduct of one molecule of trimethylolpropane to three molecules of isophorone diisocyanate, the adduct of one molecule of pentaerythritol to four molecules of toluene diisocyanate, the isocyanurate of hexamethylene diisocyanate (Desmodur® N3390, formerly Bayer), the uretdione of hexamethylene diisocyanate (Desmodur® N3400, formerly Bayer), the allophonate of hexamethylene diisocyanate (Desmodur® LS 2101, formerly Bayer), and the isocyanurate of isophorone diisocyanate (Vestanate® T1890, formerly Huels). Furthermore, (co)polymers of isocyanate-functional monomers are suitable for use, such as α,α′-dimethyl-m-isopropenyl benzyl isocyanate. Finally, the abovementioned isocyanates and their adducts may also be present in the form of blocked or latent isocyanates.

[0023] In one preferred embodiment, the film-forming resin is a hydroxyl-functional resin and the curing agent comprises isocyanate functionality, hi another preferred embodiment, the film-forming resin comprises epoxy functionality and the curing agent comprises amine functionality.

[0024] The coating composition may be a one-component or two-component (2K) composition, or a composition having three or more components. Preferably, the composition is a 2K composition. A 2K coating composition consists of two components that are stored separately and mixed immediately before application to a substrate. Typically, the first component contains an organic film-forming resin and the second component contains a hardener.

[0025] The coating compositions for use in the present invention include a lithium salt that has limited solubility in water.

[0026] The lithium salt has a solubility in water of at least 0.01, preferably 0.05, more preferably at least 0.1 g / L, measured in water at 20°C. Lithium salts with a solubility of at least 0.5, more preferably at least 1, even more preferably at least 5 g / L show particularly good results. Lithium salts with a solubility of less than 0.01 g / L do not show sufficient activity. The solubility of the lithium salt is less than 120 g / L, preferably less than 100 g / L, more preferably less than 85 g / L. Too high a solubility can lead to problems in the formulation of the coating composition, for example a non-uniform coating composition, which can lead to problems in application. The lithium salt has a solubility in the range of 0.01 to 120 g / L, measured in water at 20°C. The solubility is preferably in the range of 1 to 100 g / L. The solubility in water is measured according to OECD Guideline No. 105, EU method A.6 (flask method, procedure §23), which describes the preparation of a saturated solution, after which the concentration in the solution is measured by a suitable analytical method. Suitable analytical methods for determining the concentration of the relevant ions are known to the skilled person and can be selected depending on the ion. In particular, for lithium salts, the inductively coupled plasma mass spectrometry (ICP-OES) method is used.

[0027] The lithium salt is selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate. References herein to phosphates are references to orthophosphates unless otherwise indicated. The solubility of lithium carbonate in water is 13 g / L, lithium phosphate 0.39 g / L, lithium oxalate 62 g / L, and lithium tetraborate 28 g / L, all at 20° C. Preferably, the lithium salt is selected from the group consisting of lithium carbonate, lithium phosphate, lithium oxalate, and any mixture of two or more thereof. In some embodiments, lithium carbonate is the preferred salt. It can be used alone or in mixture with other lithium salts, such as lithium carbonate and lithium phosphate. In other embodiments, lithium phosphate may be preferred.

[0028] The coating composition preferably does not include lithium salts having a solubility of less than 0.01 g / L at 20° C. In another embodiment, the coating composition preferably does not include lithium salts having a solubility in water of more than 120 g / L at 20° C., such as lithium chloride or lithium nitrate. Preferably, the coating composition does not include any lithium salts other than lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate.

[0029] For best results, the lithium salt selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate is preferably present in the coating composition in an amount of at least 1.3 wt.%, more preferably at least 1.6 wt.%, even more preferably at least 2 wt.%, more preferably at least 2.5 wt.%, even more preferably at least 3 wt.% lithium based on the solids weight of the resin system. "Solids weight of resin system" refers to the total dry weight of the resin system, i.e., all film-forming resins in the coating composition, and the hardener, if present. The amount of lithium salt selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate in the coating is such that the weight of lithium is preferably in the range of 1.3 to 40 wt.%, based on the solids weight of the resin system. The coating composition preferably does not contain more than 40 wt.%, or more than 30 wt.%, or more than 25 wt.%, or more than 20 wt.%, or more than 15 wt.%, or more than 10 wt.% lithium based on the solids weight of the resin system. Below 1.3 wt% lithium, the protective layer may not be sufficiently strengthened, especially when lithium carbonate is used as the lithium salt. At the upper limit, it may not be practical to include more lithium in the composition due to cost and because the effect is already achieved at low concentrations. When the lithium salt is lithium phosphate, the lithium phosphate is preferably present in an amount of at least 2.0 wt%, more preferably at least 3.0 wt%, even more preferably at least 4.0 wt%, and even more preferably at least 5.0 wt% lithium, based on the weight of the solids of the resin system.

[0030] The coating composition further comprises a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD). The zinc salt of DMTD may be present by itself or as part of a hybrid compound. References herein to hybrid compounds (sometimes referred to as hybrid pigments) are inseparable intimate blends of two or more solid compounds, including both organic and inorganic compounds, typically formed by coprecipitation. Examples of hybrid compounds include host-guest compounds, where the host matrix is ​​inorganic and has a layered structure, and the guest compound is organic. However, in some embodiments, it may be preferred that the zinc salt of DMTD does not form part of the hybrid pigment.

[0031] The zinc salt of DMTD is 2,5-dimercapto-1,3,4 thiadiazole zinc salt (VII) (CAS 63813-27-4), which is a 1:2 salt of Zn and DMTD. The reference "1:2 salt" means herein that it is formed from 1 mole of Zn and 2 moles of DMTD. The salt is further referred to herein as Zn(DMTD)2 or "zinc salt of DMTD". The zinc salt of DMTD can be obtained by known methods, for example by reacting ZnO with DMTD as described in Example 1 of WO 02 / 092880. The zinc salt of DMTD is commercially available, for example as part of Inhibicor 1000 by WPC Technologies. The solubility of Zn(DMTD)2 in water is reported to be 0.4 g / L at 24°C.

[0032] In some embodiments, the zinc salt of DMTD is present in the coating composition in the absence of any further zinc-containing compounds, such as zinc oxide and / or zinc salts, such as zinc orthophosphate or zinc cyanamide (CH2N2Zn). In particular, the coating composition does not contain ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof. In some embodiments, the coating composition does not contain ZnO. In some embodiments, the coating composition does not contain zinc orthophosphate. In yet other embodiments, the coating composition does not contain zinc cyanamide. In some embodiments, the composition does not contain ZnO, zinc orthophosphate, and zinc cyanamide. Without wishing to be bound by any theory, it is believed that Zn(DMTD)2 alone plays a role in enhancing the barrier properties of the protective layer formed by the lithium ions in the lithium salt, and therefore the presence of other Zn compounds is not necessary.

[0033] However, in other embodiments, it may be beneficial for the coating composition to include an additional zinc-containing compound, such as ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof. Examples of combinations are Zn(DMTD)2 and ZnO, or Zn(DMTD)2 and zinc orthophosphate, or Zn(DMTD)2 and zinc cyanamide. When Zn(DMTD)2 is present in combination with an additional zinc compound, the amount of Zn(DMTD)2 is 1-99% by weight, preferably 10-98% by weight, more preferably 20-95% by weight, and most preferably 30-90% by weight, based on the total weight of the zinc compounds.

[0034] In some embodiments, the content of Zn(DMTD)2 in the mixture with other zinc compounds can be 50% by weight, preferably more than 60% by weight, more preferably more than 70% by weight, most preferably more than 80% by weight, more preferably more than 90% by weight, based on the solids weight of the mixture. An example of a suitable mixture is 1-30% by weight of Zn orthophosphate, 1-20% by weight of ZnO, and at least 50% by weight, for example 50-98% by weight of Zn(DMTD)2, based on the solids weight of the mixture. A much lower content of Zn(DMTD)2 in the Zn compound mixture may result in insufficient protection, especially when the DMTD content in the coating composition is less than 0.05% by weight, based on the solids weight of the resin system.

[0035] In some embodiments, Zn(DTMD)2 is present in combination with other zinc compounds, such as ZnO, zinc orthophosphate, zinc cyanamide, or any combination thereof, and the amount of Zn(DTMD)2 in said mixture is greater than 50 wt.-%, preferably greater than 60 wt.-%, more preferably greater than 80 wt.-%, and most preferably greater than 90 wt.-%, based on the weight of the solids of the mixture, and the DMTD content in the coating composition is at least 0.05 wt.-%, preferably at least 1 wt.-%, and more preferably at least 2 wt.-%, based on the weight of the solids of the resin system.

[0036] Preferably, the zinc salt of DMTD is present in the coating composition to provide at least 0.05 wt% DMTD, more preferably at least 0.1 wt%, even more preferably at least 0.4 wt%, or at least 0.6 wt%, or at least 1 wt%, more preferably at least 2 wt% or at least 4 wt% DMTD based on the solids weight of the resin system. Preferably, the amount is less than 50 wt%, or less than 40 wt%, or less than 30 wt%, or less than 20 wt% DMTD based on the solids weight of the resin system. When used in an amount less than 0.05 wt%, the synergy with lithium is believed to be too low to actually provide any benefit. Using an amount greater than 50 wt% is believed to be impractical, for example, due to potential formulation problems or high cost.

[0037] The coating composition preferably contains the lithium salt and the zinc salt of DMTD in an amount such that the weight ratio of lithium to DMTD, calculated as the weight ratio of the lithium content to the DMTD content, is 0.01 to 20, preferably 0.1 to 10. In some embodiments, it may be preferred that the content of DMTD (present as the zinc salt of DMTD) is equal to or greater than the content of lithium (present as the lithium salt). In other embodiments, it may be preferred that the content of DMTD (present as the zinc salt of DMTD) is equal to or less than the content of lithium (present as the lithium salt).

[0038] As discovered by the inventors and demonstrated in the examples, the combination of a lithium salt in an organic coating with a zinc salt of DMTD shows an unexpected enhancement of the barrier properties of the protective layer formed on an exposed metal substrate. The protective layer is formed at locations where coating defects occur, which in the examples are simulated by a scribe that penetrates the coating and exposes the base metal to the environment. Unlike other known corrosion inhibitors, lithium salts are known to form an irreversible protective layer on metal substrates (e.g., aluminum alloys) via a mechanism of leaching from the coating matrix. The protective layer provides a barrier between the metal substrate and the environment. The barrier function of this layer is not visible to the naked eye, but can be measured using electrochemical impedance spectroscopy (EIS). The presence of Zn(DMTD)2 in the coating composition with the lithium salt and organic film-forming resin results in a much higher impedance value for the protective layer than when only the lithium salt is used or when the lithium salt is used with the other screened potentially active compounds. A higher impedance value means that the protective layer has a higher barrier function or is "enhanced". The enhanced protective layer can provide improved or longer-lasting protection. This enhancement of the protective layer is unexpected since Zn(DMTD) 2 does not exhibit barrier properties or protective layer formation itself, as supported by the examples below.

[0039] The coating composition may further comprise at least one magnesium compound. Suitable magnesium compounds are magnesium-containing materials, such as magnesium metal, magnesium oxide, magnesium oxyaminophosphate salts (e.g., Pigmentan® 465M), magnesium carbonate, and magnesium hydroxide. Magnesium metal is preferably used in the form of particles, such as powder, flakes, spheres, or spheroids. It should be noted that magnesium metal and magnesium metal alloy particles require specific stabilizers when used in aqueous coating compositions. Such stabilizers are generally known and commercially available. Preferably, magnesium oxide is used as the magnesium compound.

[0040] The magnesium compound is preferably present in the coating composition in an amount of 0.1 to 50% by weight, more preferably 1 to 35% by weight, and most preferably 5 to 20% by weight, based on the dry weight of the coating composition (the sum of the weights of the non-volatile components of the coating composition).

[0041] The magnesium oxide or magnesium salt is preferably present in an amount such that the weight ratio of Mg:Li is at least 0.1:1, more preferably at least 0.5:1, even more preferably at least 1:1, and even more preferably at least 3:1. This ratio is preferably less than 30:1, more preferably less than 25:1, even more preferably less than 15:1, and even more preferably less than 10:1, and most preferably less than 8:1.

[0042] When magnesium metal or alloy is present in the composition according to the invention, the weight ratio Mg:Li is preferably less than 500:1, more preferably less than 300:1, even more preferably less than 250:1, even more preferably less than 100:1, even more preferably less than 50:1 and most preferably less than 25:1.

[0043] Preferably, the composition contains a combination of the lithium salt, magnesium oxide, and zinc salt of DMTD described above, preferably in a weight ratio of (1-5):(1-2):1, preferably about 3:1.5:1, for the lithium salt, magnesium oxide, and zinc salt of DMTD, respectively.

[0044] In some embodiments, the coating composition further comprises one or more additional corrosion inhibitors. The additional corrosion inhibitors can be organic or inorganic. Examples of inorganic inhibitors are phosphates, such as zinc orthophosphate, zinc orthophosphate hydrate, zinc aluminum orthophosphate; polyphosphates, such as strontium aluminum polyphosphate hydrate, zinc aluminum polyphosphate hydrate, magnesium aluminum polyphosphate, zinc aluminum triphosphate, and magnesium aluminum triphosphate. Inhibitors further include metal oxides, such as oxides of zinc, magnesium, aluminum, lithium, molybdate, strontium, cerium, and mixtures thereof: metals such as Zn metal, Mg metal, and Mg alloys. Examples of organic inhibitors are thiol compounds and azoles, such as imidazoles, thiazoles, tetrazoles, triazoles, such as (substituted) benzotriazoles, and 2-mercaptobenzothiazole.

[0045] In some embodiments, the additional corrosion inhibitor is a thiol compound other than 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII) or an azole. An azole is a five-membered N-heterocyclic compound that contains a nitrogen atom and at least one other non-carbon atom (i.e., nitrogen, sulfur, or oxygen) as part of the ring. Examples of suitable compounds include 5-methylbenzotriazole and 2-mercaptobenzothiazole (2-MBT). Preferably, 2-MBT is present as the additional corrosion inhibitor.

[0046] Other compounds which may be present in coating compositions for use in the present invention are colour pigments (e.g. titanium dioxide or yellow iron oxide), extenders (e.g. talcum, barium sulfate, mica, calcium carbonate, silica, or wollastonite), rheology modifiers (e.g. Bentone SD 2 or organic rheology modifiers), flow and levelling agents (e.g. polysiloxane and polyacrylate levelling additives), and solvents (e.g. ketones such as methyl isobutyl ketone, aromatics such as xylene, alcohols such as benzyl alcohol, esters such as butyl acetate, and aliphatic solvents).

[0047] In a preferred embodiment, the coating composition for use in the present invention is a liquid coating composition. The composition may include a volatile liquid diluent, such as a volatile organic solvent or water. The composition may be water-based, solvent-based, or solvent-free. The term "solvent-free" is defined as including a total content of volatile liquid diluent of less than 5% by weight, including water and organic solvent. The term "water-based" is defined as including at least 50% by weight of water of the total weight of the volatile liquid diluent (including both water and organic solvent). The term "solvent-based" is defined as including an organic solvent in an amount of at least 50% by weight of the total weight of the volatile liquid diluent (including both water and organic solvent). The coating composition is preferably solvent-based.

[0048] In some embodiments, the coating composition can be substantially free of water (non-aqueous), meaning that the water content is less than 1% by weight, preferably less than 0.1% by weight, based on the total weight of the coating composition. More preferably, the coating composition is completely free of water.

[0049] The coating compositions for use in the present invention are preferably low temperature curable compositions, meaning that they are curable, i.e. capable of forming a network, at temperatures below 120° C., preferably below 100° C., more preferably below 80° C., even more preferably below 50° C., and most preferably at ambient conditions. In other embodiments, the coating compositions may be high temperature curable compositions, for example curable at temperatures of 120° C. or higher, preferably 140° C. or higher.

[0050] The non-volatile content of the coating composition is preferably 10 to 95% by weight, more preferably 25 to 75% by weight, and even more preferably 30 to 70% by weight. In the case of an aqueous coating composition, the non-volatile content is preferably in the range of 30 to 60% by weight.

[0051] The volatile organic content (VOC) of the coating composition (measured according to ASTM D3960) is preferably less than 700 g / L, such as less than 500 g / L, more preferably less than 300 g / L.

[0052] The coating composition according to the present invention can be used as an anticorrosive primer for coating non-ferrous metal substrates, such as magnesium, magnesium alloy, titanium, aluminum, aluminum alloy, and lithium-aluminum alloy substrates.Preferred non-ferrous metal substrates are aluminum alloys.Examples of suitable aluminum alloys are 2024-T3 (bare or clad), 7075-T6 (bare or clad), 2098, 2099, 2198, 6061, 6111, 6022, 5052, 5083, 5251, 5454, 7475, 7017, and 7020.

[0053] The coating composition for use in the present invention is also suitable for coating iron substrates. Examples of suitable iron substrates are cold and hot rolled steel, stainless steel 304, B952 (zinc phosphate modified), B1000 (iron phosphate modified), and zinc modified steels such as EZG 60G, EZG 60G with zinc phosphate modified, G90, and Galvanneal HIA Zn / Fe A45.

[0054] The coating compositions for use in the present invention can be used as primers, bonding primers, self-priming topcoats, intermediate coats and / or topcoats. They can also be used in coating systems in which at least two layers have the compositions described in this disclosure.

[0055] The coating compositions can be applied to substrates with or without the use of a hexavalent chromium-free pretreatment, such as a sol-gel system such as AC-® 131 (AC Tech), PreKote® (Pantheon Chemical), or a conversion treatment.

[0056] The coating composition may also be applied to anodized surfaces, such as chromate anodized (CAA) surfaces, tartaric acid sulfuric acid anodized (TSA) surfaces, sulfuric acid anodized (SAA) surfaces, phosphoric acid anodized (PAA) surfaces, phosphoric acid sulfuric acid anodized (PSA) surfaces, and borosulfuric acid anodized (BSAA) surfaces.

[0057] The coating composition can be advantageously used as a primer coating for non-ferrous metal substrates. It can be applied as a single layer or multiple layers. In a preferred embodiment, the coating composition is applied to the substrate to form at least one primer layer in a multi-layer coating system. The topcoat layer applied over the primer layer can be a clearcoat or a pigmented topcoat. Alternatively, the coating system can also include a color and / or effect-imparting basecoat applied over the primer layer and a clearcoat applied over the basecoat. The composition can also be used as a topcoat, the topcoat being either clear or pigmented.

[0058] The composition for use in the present invention can be used in a multi-layer coating system comprising at least one layer obtained from the coating composition according to the first aspect of the present invention, i.e. comprising a resin system a), a lithium salt b) and a zinc salt of DMTD. After application, components a), b) and the zinc salt of DMTD are present in a single layer. Preferably, the layer formed from the coating composition is used as a primer layer applied to a substrate, which is optionally pretreated. The topcoat may be a clearcoat or a pigmented topcoat, or the clearcoat is applied over the basecoat layer, if the topcoat comprises a color- and / or effect-imparting basecoat applied over the primer layer.

[0059] It has been found that the enhancing effect on the barrier function, as measured by EIS, of the protective layer formed on the surface of the exposed portion of the coated metal substrate (coated with a coating composition comprising a lithium salt and an organic film-forming resin as described above) is synergistic, meaning that the effect is much higher than would be expected based on the individual components, in particular, preferably at least two times higher, more preferably at least three times higher than the effect of the individual components (in this case the lithium salt and the zinc salt of DMTD).

[0060] The coating composition for use in the present invention is particularly suitable for coating metal substrates. The metal substrate may be a non-ferrous metal substrate, such as aluminum or an aluminum alloy. Alternatively, the metal substrate may be a ferrous metal substrate. The substrate may be intended for external or internal use. Examples include aircraft structural parts, aircraft cabin parts or vehicles. The coating composition is particularly suitable for use in the aerospace, automotive or coil coating industries. EXAMPLES

[0061] Chemicals used Lithium carbonate-ACS reagent, ≥99.0%, Sigma Aldrich

[0062] Desmophen 650 MPA - a branched hydroxyl-bearing polyester from Covestro AG, 65% by weight in 1-methoxypropyl acetate-2 (MPA), 5.3% OH content

[0063] Tioxide TR 92 - Titanium dioxide from Huntsman

[0064] Zn(DMTD)2 - prepared according to Example 1 of WO 02 / 092880 A1

[0065] Hybrid 1 - A hybrid pigment prepared according to Example 2 of WO 02 / 092880 A1, containing 45 wt. % Zn(DMTD)2, 32 wt. % Zn3(PO4)2.H2O, 23 wt. % ZnO (% by weight based on the total weight of the mixture)

[0066] Hybrid 2 - a hybrid pigment prepared according to Example 1 of WO 2008 / 140648 A9, containing a neutralized salt of Zn(DMTD)2 neutralized with the disodium salt of DMTD (Na2(DMTD)), with an estimated content of 97% by weight of Zn(DMTD)2.

[0067] Hybrid 3 - a hybrid pigment prepared as Hybrid 1 but containing 75 wt. % Zn(DMTD)2, 14 wt. % Zn3(PO4)2.H2O, and 11 wt. % ZnO (% by weight based on the total weight of the mixture).

[0068] Hybrid 4 - a hybrid pigment prepared as Hybrid 1 but containing 15 wt. % Zn(DMTD)2, 49 wt. % Zn3(PO4)2.H2O, and 36 wt. % ZnO (% by weight based on the total weight of the mixture).

[0069] Hybrid 5 - prepared as Hybrid 1, but with 0 wt% Zn(DMTD)2, 58 wt% Zn3(PO4)2.H2O, and 42 wt% ZnO (wt% based on the total weight of the mixture); Hybrid 6 - prepared as Hybrid 1, but without phosphate, with 75 wt% Zn(DMTD)2 and 25 wt% ZnO (wt% based on the total weight of the mixture);

[0070] Hybrid 7 - a hybrid pigment prepared as Hybrid 1, but without phosphate, containing 45 wt. % Zn(DMTD)2 and 55 wt. % ZnO (% by weight based on the total weight of the mixture)

[0071] Hybrid 8 - a hybrid pigment prepared as Hybrid 1, but without phosphate, containing 15 wt. % Zn(DMTD)2 and 85 wt. % ZnO (wt. % based on the total weight of the mixture)

[0072] Hybrid 9 - a hybrid pigment prepared as Hybrid 1, but without phosphate, containing 7 wt. % Zn(DMTD)2 and 93 wt. % ZnO (wt. % based on the total weight of the mixture)

[0073] Airwhite AW 15 - Barium Sulfate from Sibelco Specialty Minerals

[0074] Desmodur N-75 MPA / X-Aliphatic polyisocyanate resin based on hexamethylene diisocyanate (HDI), dissolved in n-butyl acetate and xylene (1:1) from Covestro AG, solids content 75% by weight, NCO content 16.5%

[0075] Silquest A-187 - an epoxy-functional silane from Momentive Performance Materials

[0076] Electrochemical Impedance Spectroscopy (EIS) The barrier properties of the protective layer in the defect area were quantified and evaluated using electrochemical impedance spectroscopy (EIS) as described in Non-Patent Document 1: Visser, P., Liu, Y., Terryn, H. et al. “Lithium salts as leachable corrosion inhibitors and potential replacement for hexavalent chromium in organic coatings for the protection of aluminum alloys” J Coat Technol Res 13, 557-566 (2016)

[0077] EIS measurements were performed at open circuit potential (OCP) using a computer-controlled potentiostat over a frequency range of 0.01 Hz to 30,000 Hz, measuring seven points during a tenfold increase in frequency, applying a sinusoidal amplitude of 10 mV. Measurements were performed using a three-electrode configuration in a Faraday cage with a saturated calomel electrode (SCE) as the reference electrode, platinum gauze as the counter electrode, and a scribe panel as the working electrode, using 0.05 M NaCl electrolyte. The area exposed to the electrolyte was 12.5 cm. 2 and the effective bare electrode (i.e., coating defect) area is 0.48 cm 2 and the volume of the electrolyte is 60 cm 3Measurements were recorded after 2 hours of exposure to 0.05 M NaCl electrolyte for at least three samples.

[0078] The results of the examples are presented in the form of a table with Zmod values ​​at 10 mHz and 10 Hz. The higher the impedance value, the stronger the protective layer.

[0079] Preparation of test panels Unless otherwise stated, the test panels are AA2024-T3 bare aluminum alloy, typically 7.0 cm by 7 cm (3 by 6 in) and 0.8 mm thick, anodized in tartaric sulfuric acid (TSA) in accordance with aerospace requirements (AIPI 02-01-003).

[0080] The ingredients of Component A were added sequentially to a 370 ml glass jar with stirring. Then, 400 grams of Zirconox pearls (1.7-2.4 mm) were added to the mixture for grinding and dispersion of the pigment. The sample was shaken for 20 minutes in a Skandex paint shaker to achieve a grinding degree of less than 25 μm. After shaking, the pearls were separated from the coating. Component B was prepared separately by mixing.

[0081] Component B is added to component A under stirring to ensure sufficient mixing to obtain a homogenous sample. After mixing of the separate components, the coating is allowed to induce for 30 minutes.

[0082] The coatings were applied at ambient conditions (23°C, 55% RH) using a high volume, low pressure (HVLP) spray gun. After coating and a 1-hour flash-off period, the coated panels were cured at 80°C for 1 hour and dried under ambient conditions for 7 days. The dry film thickness of the coating after drying was 20-25 μm. The coated panels were scribed (cross scribe 2 cm x 2 cm) using a mechanical milling device, leaving a U-shaped scribe (cross scribe 2 cm x 2 cm) with a width of 1 mm and a depth of 100-150 μm. After scribing, the samples were exposed to a neutral salt spray test (ASTM-B117) for 168 hours.

[0083] Example 1: Synergistic effect of Li salt and Zn(DTMD)2 Formulations 1-1 to 1-4 were prepared using the components listed in Table 1. The component contents are given in parts by weight (g), and the contents of the active components Li and DMTD are given as weight % based on the resin system solids.

[0084] The ingredients of Component A were added sequentially to a 370 ml glass jar with stirring. Then, 400 grams of Zirconox pearls (1.7-2.4 mm) were added to the mixture for grinding and dispersion of the pigment. The sample was shaken for 20 minutes in a Skandex paint shaker to achieve a grinding degree of less than 25 μm. After shaking, the pearls were separated from the coating. Component B was prepared separately by mixing.

[0085] Component B was added to Component A under stirring to ensure sufficient mixing to obtain a homogenous sample. After mixing of the separate components, the coating was allowed to induce for 30 minutes.

[0086] [Table 1]

[0087] Formulations 1-1, 1-2, and 1-3 are comparative formulations, and formulation 1-4 is in accordance with the present invention. The results of the EIS measurements are shown in FIG.

[0088] It can be seen that the coatings containing both Zn(DMTD)2 and a Li salt (1-4) exhibit significantly higher impedance |Z| (also referred to as "Zmod") values ​​than the formulation without any active ingredient (1-1), or the formulations containing only Zn(DMTD)2 (1-2) or only the Li salt (1-3).

[0089] This effect is much stronger than the sum of the individual effects of the Li salt (1-3) and Zn(DMTD)2 (1-2) and is therefore a synergistic effect.

[0090] The results also show that Zn(DMTD)2 alone (1-2) does not affect the formation of a protective layer in the defect area. In particular, the coating 1-2 has a low impedance value comparable to that of the no coating (negative reference) (1-1).

[0091] Example 2: Comparison with other azoles Formulations 2-1 through 2-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 2. The ingredient contents are given in parts by weight (g). The active ingredient contents are also given as weight % based on the resin system solids. The molar amount of the azole is the same across all formulations in this example. BTA is benzotriazole and 2-MBT is 2-mercaptobenzothiazole.

[0092] [Table 2]

[0093] Formulations 2-1, 2-2, 2-3, 2-4, 2-5, 2-6 are comparative formulations and formulation 2-7 is in accordance with the present invention. The results of the EIS measurements are shown in FIG.

[0094] The results also show that the combination of Li salts with other azoles (BTA or 2-MBT) does not have the same synergistic effect as the combination with Zn(DMTD)2, which provides much higher impedance values ​​associated with a strengthened protective layer in the defect areas.

[0095] Example 3: Zn(DMTD)2 in hybrid pigments Formulations 3-1 through 3-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 3. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0096] [Table 3]

[0097] Formulations 3-1, 3-2, 3-3 and 3-4 are comparative formulations, while formulations 3-5, 3-6 and 3-7 are in accordance with the present invention. The results of the EIS measurements are listed in Table 3.

[0098] The results show that when Zn(DMTD)2 is incorporated into the hybrid pigment, it has the same effect with the lithium salt as Zn(DMTD)2 used as a pure component. In all formulations, the total amount of Zn(DMTD)2 in the coating is the same.

[0099] Example 4: Different ratios of Zn(DMTD)2 in hybrid pigments Formulations 4-1 through 4-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 4. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0100] [Table 4]

[0101] Formulations 4-1, 4-2 and 4-6 are comparative formulations, while formulations 4-3, 4-4, 4-5 and 4-7 are in accordance with the invention. The results of the EIS measurements are listed in Table 4.

[0102] In these examples, the weight ratio of Zn(DMTD)2 in the hybrid pigment varies from low to high, but the amount of Zn(DMTD)2 in the coating is the same. All examples with hybrid pigments containing Zn(DMTD)2 show the strengthening effect of the protective layer in the defective area. There is little difference in the strengthening of the different hybrid pigments. Therefore, this effect does not depend on the presence and amount of ZnO or Zn3(PO4)2.

[0103] Example 5: Alternative hybrid pigment; combination of ZnO and Zn(DMTD)2 Formulations 5-1 through 5-7 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 5. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0104] [Table 5]

[0105] Formulations 5-1 and 5-2 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 5.

[0106] In these examples, Li salts are combined with hybrid pigments based only on Zn(DMTD)2 and ZnO. The amount of Zn(DMTD)2 is the same in all examples and all samples show the same effect of strengthening the protective layer. It can be concluded that the presence of ZnO does not affect the synergistic effect between Li and Zn(DMTD)2. The synergistic effect is due to the combination of Li salts with Zn(DMTD)2.

[0107] Example 6: Alternative hybrid pigment; combination of ZnO and Zn3(PO4)2 Formulations 6-1 through 6-5 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 6. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0108] In these experiments, the performance of alternative hybrid pigments containing ZnO and Zn3(PO4)2, with and without Zn(DTMD)2, is investigated.

[0109] [Table 6]

[0110] Formulations 6-1, 6-2 and 6-3 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 6.

[0111] It can be concluded that the combination of ZnO and Zn3(PO4)2 hybrid pigments with Li salts has no synergistic effect on the barrier effect of the protective layer. Only the presence of Zn(DMTD)2 in this formulation provides the effect according to the invention.

[0112] Example 7: Effect of ZnO Formulations 7-1 to 7-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 7. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0113] In these experiments, the effect of ZnO is investigated. Examples include ZnO with and without Li salts and / or Zn(DTMD)2. They are used in the form of a physical mixture, not as part of a hybrid pigment.

[0114] [Table 7]

[0115] Formulations 7-1, 7-2, 7-3 and 7-4 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 7.

[0116] As can be seen from the EIS results, ZnO alone does not show any synergistic effect with the Li salt. From this example, it can be concluded that Zn(DMTD)2 is necessary to have a strengthening effect on the protective layer.

[0117] Example 8: Effect of Zn3(PO4)2 Formulations 8-1 through 8-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 8. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0118] In these experiments, exemplary formulations include Zn3(PO4)2, with or without Li, and Zn(DTMD)2. They are used in the form of a physical mixture, not as part of a hybrid pigment.

[0119] [Table 8]

[0120] Formulations 8-1, 8-2, 8-3 and 8-4 are comparative formulations, while 8-5 and 8-6 are according to the invention. The results of the EIS measurements are listed in Table 8.

[0121] As can be seen from the results, Zn3(PO4)2 alone did not show any strengthening effect with Li salt in the formation of a protective layer in the defect area. The addition of Zn(DMTD)2 to the formulation containing Li salt is necessary to have a synergistic strengthening effect on the barrier properties of the protective layer.

[0122] Example 9: Combination of ZnO and Zn3(PO4)2 Formulations 9-1 to 9-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 9. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0123] In these experiments, the coating composition contains ZnO and Zn3(PO4)2, with or without Li, and Zn(DTMD)2. The ratio of ZnO to Zn3(PO4)2 is the same as in Hybrid 1, but is used in the form of a physical mixture rather than as part of the hybrid pigment.

[0124] [Table 9]

[0125] Formulations 9-1, 9-2, 9-3 and 9-4 are comparative formulations, while 9-5 and 9-6 are according to the invention. The results of the EIS measurements are listed in Table 9.

[0126] As can be seen from the results, the combination of ZnO and Zn3(PO4)2 does not show any strengthening effect with Li salts. The addition of Zn(DMTD)2 is necessary to obtain the strengthening effect of the protective layer in the defect area.

[0127] Example 10: Li salts of different concentrations Formulations 10-1 to 10-8 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 10. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0128] In these experiments, the formulations contained Li salt and Zn(DTMD)2, with varying concentrations of the Li salt.

[0129] [Table 10]

[0130] Formulations 10-1, 10-2, 10-3, 10-4 and 10-5 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 10.

[0131] It can be seen that significantly higher impedance values ​​are obtained for compositions containing at least 1.3 wt. % Li relative to the resin system solids in combination with Zn(DMTD)2 compared to samples containing only Li salts.

[0132] Example 11: Different Concentrations of Zn(DMTD)2 Formulations 11-1 to 11-8 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 11. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0133] In these experiments, the active materials include Li salt and Zn(DTMD)2 with various concentrations of Zn(DTMD)2.

[0134] [Table 11]

[0135] Formulations 11-1, 11-2 and 11-3 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 11.

[0136] It can be concluded that Zn(DTMD)2 shows a synergistic effect with any amount of Li salt, even at very small amounts of DMTD, such as 0.6 wt.%, that even at these low concentrations of DMTD there is a clear improvement (strengthening effect) of the barrier properties of the protective layer in the defect areas.

[0137] Example 12: Different Li salts (4.4% Li) Formulations 12-1 to 12-8 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 12. The amount of ingredients is given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0138] In these experiments, the coatings contained different soluble Li salts, with a Li content of 4.4 wt. % based on the resin system solids. The lithium salts were chosen with different solubilities.

[0139] [Table 12]

[0140] Formulations 12-1 to 12-5 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 12.

[0141] It can be concluded that Zn(DTMD)2 shows a reinforcing effect with Li salts whatever the salt used. The moderate effect on lithium phosphate is likely due to its low solubility in water.

[0142] Example 13: Different Li salts (1.3 wt% Li) Formulations 13-1 to 13-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 13. The ingredient amounts are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0143] In these experiments the coating composition contained different soluble Li salts with a Li content of 1.3 wt. % based on the resin system solids.

[0144] [Table 13]

[0145] Formulations 13-1 to 13-3 are comparative formulations, the other formulations are according to the invention. The results of the EIS measurements are listed in Table 13.

[0146] It can be concluded that Zn(DTMD)2 shows enhanced protective layers for most Li salts, even when used in amounts less than in Example 12, except for lithium phosphate, for which better results were achieved with higher Li content (Example 12), which is likely due to its lower solubility in water.

[0147] Example 14: No Magnesium Oxide Formulations 14-1 to 14-4 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 14. The amount of ingredients is given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0148] These experiments test whether the strengthening effect is also present in compositions that do not contain magnesium oxide.

[0149] [Table 14]

[0150] Formulations 14-1 through 14-3 are comparative formulations and 14-4 is in accordance with the present invention. The results of the EIS measurements are listed in Table 14.

[0151] It can be concluded that the strengthening effect exists even in the absence of MgO and is purely due to the combination of the lithium salt with Zn(DMTD)2.

[0152] Example 15: Lithium phosphate at different concentrations Formulations 15-1 to 15-6 were prepared in the same manner as Example 1, but with the ingredients as shown in Table 15. The amounts of ingredients are given in parts by weight (g). The amount of active ingredient is also given as weight % based on the resin system solids.

[0153] In these experiments, the concentration of lithium phosphate is varied so that the Li content of the resin-based solids is 2.0 to 7.0 wt.

[0154] [Table 15]

[0155] Formulations 15-1 to 15-3 are comparative formulations, and the other formulations are according to the invention. Test panels were prepared and scribed as described above. After scribing, the samples were exposed to a neutral salt spray test (ASTM-B117) for 96 hours. The results of the EIS measurements are listed in Table 15. The present invention includes the following aspects. Section 1. 1. Use of a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the zinc salt of DMTD being 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII), comprising a metal salt thereof and a) a resin system comprising an organic film-forming resin and optionally a curing agent reactive with said organic film-forming resin; b) a lithium salt having a solubility in water in the range of 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; In a coating composition further comprising To enhance the barrier function of a protective layer produced as a result of the presence of said lithium salt in said coating composition when used on a metal substrate coated with said coating composition. Use of the zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD). Section 2. Item 2. The use according to item 1, wherein the coating composition does not contain any zinc-containing compound other than the zinc salt of DMTD. Section 3. Item 2. The use according to item 1, wherein the coating composition further comprises a zinc-containing compound selected from the group consisting of zinc oxide, zinc phosphate, zinc cyanamide, and any combination thereof. Section 4. The use according to any one of items 1 to 3, wherein the lithium salt is lithium carbonate. Section 5. Item 5. The use according to any one of items 1 to 4, wherein the lithium salt is present in an amount of at least 1.3% by weight lithium based on the resin system solids. Section 6. Item 5. The use according to any one of items 1 to 4, wherein the lithium salt b) is lithium phosphate, and the lithium phosphate is present in an amount of at least 2.0% by weight, preferably at least 3.0% by weight, more preferably at least 4.0% by weight, of lithium, based on the resin system solids. Section 7. 7. The use according to any one of items 1 to 6, wherein the zinc salt of DMTD is present in an amount of 0.05 to 20% by weight of DMTD based on the resin system solids. Section 8. Item 8. The use according to any one of items 1 to 7, wherein the film-forming resin is selected from the group consisting of epoxy resins, hydroxy-functional poly(meth)acrylates, polyester polyols and polyurethanes. Section 9. The use according to any one of items 1 to 8, wherein the coating composition further comprises a thiol or azole other than 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII). Section 10. Use according to any one of claims 1 to 9 in a multi-layer coating system on a metal substrate, wherein the coating system comprises a layer obtained from the composition according to any one of claims 1 to 9. Section 11. Item 11. The use in a multi-layer coating system according to item 10, wherein the layer obtained from the coating composition according to any one of items 1 to 9 is a primer layer on the metal substrate.

Claims

1. 1. Use of a zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD), the zinc salt of DMTD being 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII), comprising: a) a resin system comprising an organic film-forming resin and optionally a curing agent reactive with said organic film-forming resin; b) a lithium salt having a solubility in water ranging from 0.01 to 120 g / L at 20° C. selected from the group consisting of lithium carbonate, lithium phosphate, lithium bicarbonate, lithium tetraborate, and lithium oxalate; In a coating composition further comprising To enhance the barrier function of a protective layer on a metal substrate coated with the coating composition, the protective layer being formed as a result of the presence of the lithium salt in the coating composition. Use of the zinc salt of 2,5-dimercapto-1,3,4-thiadiazole (DMTD).

2. 2. The use according to claim 1, wherein the coating composition does not contain any zinc-containing compounds other than the zinc salt of DMTD.

3. 2. The use of claim 1, wherein the coating composition further comprises a zinc-containing compound selected from the group consisting of zinc oxide, zinc phosphate, zinc cyanamide, and any combination thereof.

4. 2. The use according to claim 1, wherein the lithium salt is lithium carbonate.

5. 2. The use according to any one of claims 1, wherein the lithium salt is present in an amount of at least 1.3% by weight lithium based on resin system solids.

6. 2. The use of claim 1, wherein the lithium salt b) is lithium phosphate, and the lithium phosphate is present in an amount of at least 2.0 wt. % lithium, based on resin system solids.

7. 2. The use of claim 1, wherein the zinc salt of DMTD is present in an amount of 0.05 to 20% by weight of DMTD based on resin system solids.

8. 2. The use according to claim 1, wherein the film-forming resin is selected from the group consisting of epoxy resins, hydroxy-functional poly(meth)acrylates, polyester polyols and polyurethanes.

9. The use according to claim 1, wherein the coating composition further comprises a thiol or azole other than the 2,5-dimercapto-1,3,4-thiadiazole zinc salt (VII).

10. 10. Use according to any one of claims 1 to 9 in a multi-layer coating system on a metal substrate, said coating system comprising a layer obtained from the composition according to any one of claims 1 to 9.

11. 11. Use in a multi-layer coating system according to claim 10, wherein the layer obtained from the coating composition according to any one of claims 1 to 9 is a primer layer on said metal substrate.

Citation Information

Patent Citations

  • Multilayer and complex corrosion-resistant coating

    JP2010520096A

  • Corrosion resistant adhesive sol-gel

    JP2018154813A

  • Curable film-forming composition containing lithium silicate as a corrosion inhibitor and a metal substrate coated with multiple layers

    JP2018524421A

  • Hybrid pigment grade corrosion inhibitor compositions and procedures

    WO1999018044A1

  • Anti-corrosive coating composition

    WO2010112605A1